Two Pillar solution for taxing the digitalized economy: Policy implications and guidance for the Global South - Irene Ovonji-Odida; Veronica Grondona; Abdul Muheet Chowdhary (South Centre, 2022)
The taxation of the digitalized economy is the single most important topic in international tax negotiations today. The OECD has devised a "Two Pillar solution" to the problem. Pillar One is focusing on a reallocation of taxing rights to market jurisdictions, which are largely expected to be developing countries, and Pillar Two is instituting a global minimum tax. The Pillar One solution, known as Amount A, will be codified into a Multilateral Convention (MLC) and is expected to be placed before countries for signature in early 2023. The solution ushers in a new paradigm in the taxation of multinational enterprises but has immense complexity and likely minimal revenue gains for most developing countries. It will also require them to give up the right of unilateral tax measures on all out-of-scope companies, meaning they will only be able to tax the fewer than 100 companies likely to be in-scope, if at all. The decision to sign or not is thus a historic one, as it will lock developing countries into a constricted new framework, at a time when revenue needs are especially critical to recover the economies from COVID-19 in the context of a turbulent state of the global economy. However, the United Nations too has a solution, known as Article 12B. This operates in a different manner and is a minor modification to the existing decentralized international tax system which is based on bilateral tax treaties, and which developing countries are more familiar with. It is also likely to generate far higher revenues than Amount A, and does not restrict any of their sovereign taxing rights. This Research Paper assesses the various implications for developing countries from adopting the OECD's or the United Nations's respective solutions and concludes with a possible global South response to the Two Pillar solution.
Keywords: 300; Amount A; Article 12B; Automated Digital Services (ADS); Base Erosion and Profit Shifting Project (BEPS); Bilateral Tax Treaties; Digital Economy; Digital Service Taxes (DSTs); Digital Tax; Digital Taxation; Double Taxation; Global Minimum Tax Rate; Global Tax; Global Taxation; Group of 20 (G-20); Group of 7 (G-7); Group of 77 and China (G-77 and China); Group of Twenty-Four (G-24); Illicit Financial Flows (IFFs); Inclusive Framework; International Tax; International Tax Cooperation; International Taxation; Multinational Enterprises (MNEs); Organisation for Economic Co-operation and Development (OECD); Pillar One; Pillar Two; Tax; Tax Cooperation; Tax Law; Tax Policy; Tax Reform; Taxation; Taxing Rights; The Multilateral Convention (MLC); Two Pillar Solution; UN Model Tax Convention; UN Tax Committee; United Nations (UN)